Rabies Risk Factor Analysis in Parigi Moutong Regency, Central Sulawesi Province in 2023 - Pitrah Asfian; Muhammad Fadil Pratama (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Rabies is a zoonotic disease transmitted through the bites of mammals infected with the Rabies lyssavirus. It remains a major public health concern in Indonesia, as several provinces continue to be endemic. The virus primarily targets the central nervous system, leading to progressive encephalopathy and, if left untreated, results in an extremely high case fatality rate. Objectives: This study aims to analyze the risk factors associated with rabies cases in Parigi Moutong Regency, Central Sulawesi, in 2023, using official health surveillance data to identify epidemiological trends and support evidence-based public health interventions. Methods: A descriptive quantitative study design was employed using secondary data obtained from the Central Sulawesi Provincial Health Profile. The data were systematically compiled and presented in graphical form to examine patterns and temporal trends in reported rabies cases. Results: The results demonstrate a notable increase in rabies cases in Parigi Moutong Regency. This rise appears to be associated with increased human–animal interactions in the post–COVID-19 period. Inadequate public awareness and suboptimal animal vaccination coverage were identified as key factors influencing rabies transmission. Conclusion: The observed increase in rabies cases in Parigi Moutong Regency underscores the urgent need to strengthen animal vaccination programs, enhance community awareness, and promote cross-sectoral collaboration. Implementing a data-driven public health strategy is essential to reduce rabies-related mortality and to support the national goal of achieving a rabies-free Indonesia by 2030.